Towards developing software testing as a service (STaaS) model in cloud computing: a case of collaborative knowledge management system - Abdullah, Rusli (2012)
Software testing (ST) is the process of identifying and delivering the software as a product based on the specification that has been given and required by the users. In order to ensure the product is working properly based on the user specification, there are many people who are working together and provide their services for a community of practice (CoP) purposes. The CoP in ST of cloud computing environment are including the software designer, programmer, and system tester as well as the software users by themselves. Based on this scenario of working together or working collaboratively in order to avoid a lot of mistakes or errors and causes the software failure, which may be found during the ST as a service (STaaS) process, so that there is a need for CoP to have a tool called Collaborative Knowledge Management System (CKMS) in managing the ST knowledge of best practice and lesson learnt. The paper will discuss a model on how the ST of CoP is offering its service of processes called STaaS through knowledge life cycle which starting from knowledge acquisition, knowledge storing, knowledge dissemination, and knowledge application in order to overcome any shortcoming faulty or failure especially during the software development and it implementation in a cloud computing environment. Therefore, by utilizing the CKMS model in managing knowledge of STaaS, the CoP can maximize the STaaS knowledge in the CKMS and furthermore to overcome the mistakes or errors, so that they can also delivered a good product as part of well services besides in enhancing the quality of software of the particular users.